2021
DOI: 10.1016/j.cub.2021.03.067
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming sphingolipid glycosylation is required for endosymbiont persistence in Medicago truncatula

Abstract: Reprogramming sphingolipid glycosylation is required for endosymbiont persistence in Medicago truncatula Highlights d Sphingolipid glycosyltransferases are differentially expressed in symbiotic tissues d MtGINT1 is expressed in cell types synthesizing perimicrobial membranes d MtGINT1 functions in N-acetyl glucosamine sphingolipid glycosylation in planta d Silencing MtGINT1 impairs nodulation and arbuscular mycorrhizal symbiosis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 74 publications
0
17
0
Order By: Relevance
“…Meanwhile, AMF are separated from the plant cytoplasm by a specialized host-derived membrane, which represents the main interface facilitating the bidirectional exchange of nutrients and information. The biosynthesis of this periarbuscular membrane is controlled by a gene called glucosamine inositol phosphorylceramide transferase 1 (Moore et al, 2021). The endophytic fungus S. indica secretes specific proteins to improve its access to micronutrients and to influence oxidative stress and reactive oxygen homeostasis to support the colonization of the host plant (Nostadt et al, 2020).…”
Section: Colonization Phasementioning
confidence: 99%
“…Meanwhile, AMF are separated from the plant cytoplasm by a specialized host-derived membrane, which represents the main interface facilitating the bidirectional exchange of nutrients and information. The biosynthesis of this periarbuscular membrane is controlled by a gene called glucosamine inositol phosphorylceramide transferase 1 (Moore et al, 2021). The endophytic fungus S. indica secretes specific proteins to improve its access to micronutrients and to influence oxidative stress and reactive oxygen homeostasis to support the colonization of the host plant (Nostadt et al, 2020).…”
Section: Colonization Phasementioning
confidence: 99%
“…2018 ). Glycosylated sphingolipids may play a role in PAM formation or the regulation of its protein composition, as a M. truncatula GLUCOSAMINE INOSITOL PHOSPHORYLCERAMIDE TRANSFERASE1 ( GINT1 ) gene required for the glycosylation of N -acetyl-glucosamine-decorated glycosyl inositol phosphoryl ceramides is required for arbuscule maturation and branching ( Moore et al. 2021 ).…”
Section: Lipid Composition Of the Pammentioning
confidence: 99%
“…Complementation of A. thaliana gmt mutants with either A. thaliana or O. sativa GINT recovered total GIPC levels, with GlcNAc replacing Hex, but only partially rescuing the developmental phenotype of these mutants. Further evidence of the significance of Hex/HexNAc content of GIPCs was recently found in the roots and nodules of the model legume Medicago truncatula by Moore et al (2021) . MtGINT1 , the gene required for transferring HexNAc headgroups to GIPCs, is expressed in tissues synthesizing perimicrobial membranes that directly interact with both bacterial (nodulating rhizobia) and fungal (arbuscular mycorrhiza) root symbionts.…”
Section: Clues From a Model Monocot: Oryza Sativamentioning
confidence: 86%
“…Profiling of diverse species by Cacas et al (2013) revealed patterns in the number of sugar headgroups added to different lineages. It is equally fascinating that multiple recent studies have uncovered specific functions for specific GIPC modifications in plant physiology and biotic interactions ( Grison et al , 2015 ; Lenarčič et al , 2017 ; Jiang et al , 2019 ; Moore et al , 2021 ).…”
Section: Introductionmentioning
confidence: 99%